Throwbacks that move us: The dance-inducing power of nostalgic songs. - Riya K Sidhu; Diana M Urian; Hong Zheng; Jessica A Grahn (PLoS ONE)
The urge to move to music, often referred to as groove, is influenced by various factors, including familiarity with the music. The influence of nostalgia, which involves familiarity but also includes pleasant, sad, and wistful emotions, remains largely unexplored. Here we investigate the impact of both familiarity and nostalgia on the desire to tap, move, and dance along to music. To evoke nostalgia, we selected popular songs from the participants' adolescent years. More recent songs served as a low-nostalgia but familiar control. Participants completed an online experiment, rating songs based on their desire for three different movement types (tap, move, and dance), as well as enjoyment, familiarity, and nostalgia. Nostalgic songs elicited higher desire to move than familiar songs across all three movement categories. Additionally, both familiarity and nostalgia predicted move and tap ratings, but only nostalgia emerged as a predictor for dance ratings. Our results suggest a distinctive role for nostalgia, beyond the influence of familiarity, in motivating the desire to dance.